Karakteristik tekstur dan sensori roti sourdough dengan penambahan Dangke (keju Enrekang) - Monika Rahardjo; Monang Sihombing; Marta Amelyia Sipayung; Bintang Carouline (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Sourdough bread is increasingly recognized not only for its nutritional benefits but also for its potential to incorporate local ingredients that improve sensory and functional qualities. Dangke (Enrekang cheese), a traditional Indonesian dairy product, contains protein and lipid components that may influence the texture and flavor profile of sourdough bread. This study aimed to evaluate the effect of Dangke incorporation on the physical and sensory characteristics of sourdough bread, with a focus on identifying the optimal concentration that enhances bread quality. Texture analysis was performed using a texture analyzer to measure hardness, cohesiveness, springiness, gumminess, chewiness, fracture force, adhesiveness, adhesive force, and stiffness and sensory analysis was conducted to assess visual, taste, aroma, texture, and overall acceptance. Statistical analysis was conducted using ANOVA and Duncan’s test. Significant differences were observed in hardness, fracture force, and stiffness, while other parameters showed no statistical differences. Moderate incorporation of Dangke (10–20%) reduced hardness and stiffness, producing softer crumb structures. However, at higher concentrations (30%), hardness and stiffness increased, likely due to competition for water absorption and disruption of gluten networks. Sensory results showed improved flavor, aroma, and overall acceptance with increasing Dangke levels, with the highest scores obtained at 20–30%. Incorporating Dangke at optimal levels (20–30%) significantly improves the sensory quality of sourdough bread while maintaining desirable texture. These findings highlight the potential of Dangke as a functional ingredient for product diversification and nutritional enrichment in sourdough-based bakery products.